Kitab-Kitab Dalam Bidang Ilmu Mukhtalif Hadis Dan Sejarah Perkembangannya - Tazkiyatul Fuadah alJunsa AlJunsa (STIU Al-Mujtama Pamekasan, 2022)
This article discusses the characters and books in the science of Mukhtalif Hadith and the Method of Completion of the Science of Mukhtalif Hadith, methods of resolving conflicting mukhtalif traditions, namely the first, authentic or hasan hadiths which outwardly seem contradictory to authentic hadiths. or other hasan. Second, Nasakh, which is to find out which of the two hadiths came first, and which came later. Third, Tarjih, which is conducting research on which hadiths are strong, both in the sanad and in their eyes, to be interpreted. How to solve this according to Imam al-Shafi'i. Hadith second order, in the system of legal sources. It works as a text that is still in the form of an outline that will limit the generality of the Nash, or establish laws that have not been clearly defined in the Qur'an. Hadith is a very noble position and Allah has greatly honored Muslims. The journey of hadith is so very long that it reaches our hands today, this is proof that Allah always protects the hadith of the Prophet until the end of time. In its journey the hadith has gone through various threats from outside Islam or from within Islam itself, where efforts to falsify hadith have never stopped, but Allah protects through thick fortresses, namely the hadith scholars and fiqh scholars who always interact with hadith sincerely and sincerely. sincerely full of love for the Prophet Muhammad. Hadith in the form of words, deeds and decisions. The Messenger of Allah is not all easy to understand, especially for us as end-time hadith students where the time is quite far from the Prophet or his companions. Mukhtalif hadith is a hadith that outwardly seems contradictory. KeyWord: Mukhtalif Hadith, hadith scholars, solution method